2016
DOI: 10.1016/j.jshs.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of core and non-dominant arm strength training on drive distance in elite golfers

Abstract: BackgroundVarious training schemes have sought to improve golf-related athletic ability. In the golf swing motion, the muscle strengths of the core and arms play important roles, where a difference typically exists in the power of arm muscles between the dominant and non-dominant sides. The purposes of this study were to determine the effects of exercises strengthening the core and non-dominant arm muscles of elite golf players (handicap < 3) on the increase in drive distance, and to present a corresponding tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
1
25
0
1
Order By: Relevance
“…Significance of arm's strength training as factors of success was confirmed in swimming (Dummer, et al, 1985), in golf (Sung, Park, Kim, Kwon, & Lim, 2014), Nordic Walking (Song, Yoo, Choi, & Kim, 2013). It was detected that maximal power training improves efficiency of muscles' work and their endurance (Kemi et al, 2010; Hassanlouei, Falla, Arendt-Nielsen, & Kersting, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Significance of arm's strength training as factors of success was confirmed in swimming (Dummer, et al, 1985), in golf (Sung, Park, Kim, Kwon, & Lim, 2014), Nordic Walking (Song, Yoo, Choi, & Kim, 2013). It was detected that maximal power training improves efficiency of muscles' work and their endurance (Kemi et al, 2010; Hassanlouei, Falla, Arendt-Nielsen, & Kersting, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…et al proved prognostic significance of arms' strength for successfulness in swimming [25]. Analogous studies were fulfilled in golf [39]. Klimczyk M. et al studied correlations between efficiency and physical parameters of pole vaulting jumpers [33].…”
mentioning
confidence: 97%
“…In addition, it has been shown that low-handicap golfers have greater activation of the right ES at the start of the downswing than highhandicap golfers [7]. Improving muscle strength of the back lumbar region leads to faster CHS [14,15]. Taking these into account, it is assumed that greater ES size, especially in the right side, leads to greater mechanical work and power production during the downswing, and consequently this may be a reason for the selection of the ES as a significant contributor for CHS.…”
Section: Discussionmentioning
confidence: 99%
“…CHS during the golf swing correlates positively with the trunk angular velocity towards the downswing direction [12,13]. Resistance exercises for the trunk muscles, such as the crunch, trunk twist, and good morning (trunk flexion/extension), are known to improve trunk muscle strength and golf driving performance [14,15]. It is also reported that the muscle volume of the lower region of the trunk in throwers significantly cor-This study examined how the volume of trunk muscles and its bilateral asymmetry are related to club head speed in golfers.…”
Section: Introductionmentioning
confidence: 99%